2018
DOI: 10.1098/rsos.180413
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of circular RNAs in Qinchuan cattle testis

Abstract: Circular RNA (circRNA) is a new class of non-coding RNA that has recently attracted researchers' interest. Studies have demonstrated that circRNA can function as microRNA sponges or competing endogenous RNAs. Although circRNA has been explored in some species and tissues, the genetic basis of testis development and spermatogenesis in cattle remains unknown. We performed ribo-depleted total RNA-Seq to detect circRNA expression profiles of neonatal (one week old) and adult (4 years old) Qinchuan cattle testes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…In mammalians, there is only limited evidence of mt-circRNAs. Gao et al (2018) found three mt-circRNAs by studying circRNAs expression in cattle testis, but their functions were not elucidated [70]. In mice, it was demonstrated that a nuclear circRNA called MFACR (mitochondrial fission and apoptosis-related circRNA) regulates mitochondrial fission and apoptosis in the heart by regulating miR-652-3p, suggesting that circRNAs are potential biomarkers of cardiovascular diseases [71].…”
Section: Circular Rnasmentioning
confidence: 99%
“…In mammalians, there is only limited evidence of mt-circRNAs. Gao et al (2018) found three mt-circRNAs by studying circRNAs expression in cattle testis, but their functions were not elucidated [70]. In mice, it was demonstrated that a nuclear circRNA called MFACR (mitochondrial fission and apoptosis-related circRNA) regulates mitochondrial fission and apoptosis in the heart by regulating miR-652-3p, suggesting that circRNAs are potential biomarkers of cardiovascular diseases [71].…”
Section: Circular Rnasmentioning
confidence: 99%
“…Circular RNAs (circRNAs), unlike miRNAs and long non-coding RNAs (lncRNAs), are a novel type of non-coding RNAs originated from introns, intergenic regions, untranslated regions and exhibit distinct patterns of alternative back-splicing and alternative splicing [107,108]. The roles of circRNAs in self-renewal and differentiation of spermatogonial stem cells and sperm motility are gradually being studied [109][110][111][112]. However, the relationships between alternative splicing that involved by circRNAs and spermatogenesis was seldom reported and needed further study.…”
Section: The Communication Between Sertoli-sertoli Cell Andmentioning
confidence: 99%
“…In addition, this organ expresses more complex transcriptomes in comparison with other tissues (Soumillon et al, 2013). Rapid advancement has demonstrated that non-coding RNAs were emerging as important regulators of gene expression at post-transcription in spermatogenesis, such as microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and Piwi-interacting RNA (piRNAs) (Mukherjee et al, 2014; Robles et al, 2017; Gao et al, 2018; Qiu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%